Analysis of Product, Promotion and People Marketing Mix on Customer Decisions in the Use of Mobile Banking at Bank Mandiri Prabumulih South Sumatra Province Inpress Market Branch Office - Yanto, Rudi; Helmi, Sulaiman; Trisninawati; Sharif, M. Amiruddin (Indonesian Scientific Publication, 2024)
Competition in the banking industry in Indonesia is getting tighter with the number of banking institutions operating. To compete, banks need to have a competitive advantage through the adoption of information technology and quality services. Bank Mandiri, especially Prabumulih Inpress Market Branch Office, has implemented mobile banking as one of the efforts to improve services to customers. However, the effectiveness of the marketing mix (products, promotions, and people) in encouraging customers' decisions to use mobile banking services still needs further research. This study aims to investigate the influence of marketing mix strategy on the decision to use mobile banking at Bank Mandiri Prabumulih Inpress Market Branch Office. Through the analysis of primary data collected from customers, this study is expected to provide deeper insights into the factors that affect mobile banking adoption. The results of the research are expected to make a strategic contribution in increasing the effectiveness of the promotion and use of mobile banking services, as well as strengthening Bank Mandiri's image in the eyes of customers.